Space debris and satellite laser ranging combined using a megahertz system - Michael A. Steindorfer; Peiyuan Wang; Franz Koidl; Georg Kirchner (Nature Communications)
Abstract Satellite laser ranging and space debris laser ranging are two closely related range measurement techniques with slightly different setups relying on different lasers. Satellite laser ranging measures light reflections of corner cube retro reflectors at mm-level range precision. Space debris laser ranging gathers diffuse reflections from the whole space debris object and offers a precision down to the sub meter-level. Within this work we show the usage of Megahertz lasers to combine the strengths of both systems within one setup. During the regular tracking schedule to scientific satellite laser ranging targets, specific space debris objects of interest can then be tracked without the need of making adaptions to the system. Megahertz satellite laser ranging measurements to the defunct Jason-2 satellite lead to a measurement precision down to a few μm when ranging to retro reflectors. Space debris laser ranging data reveals reflections from individual surfaces of the target and allows to draw conclusions on the rotational behavior.